BІМ as a tool for reforming the pricing system in construction (on the example road construction companies in Кazakhstan) - Tsyfra, Т. (Ways to Improve Construction Efficiency, 2021)
The article reflects the experience of the Republic of Kazakhstan on the implementation of the concept of BIM as one of the tools for reforming the pricing system of road construction companies in the context of historical retrospect. Particular attention is paid to the already implemented stages of implementation of information modeling technology for construction projects (TIMBO) in the road industry. The resource method of determining the estimated cost will allow you to more accurately calculate the estimate in the early stages of the project and then assess how justified in the TIMBO model a project decision, and whether it leads to unjustified increase in costs in the budget documentation. Progress in the development of computer-aided design technologies in road construction places increasing demands on the creation of 3D interface design system (BIM) systems with the evaluation and economic section of the 5D project in the ABC-4 program. Since 2017, Kazakhstan is introducing new methods in the development of budget documentation in ABC-4, BIM-systems Autodesk Revit, Nemetschek Allplan and Renga Architecture, methods of developing estimates for multi-platform BIM-design with cost formation, using as a state system of budget standards, and the corporate base of norms and prices for road construction. Within the framework of the RK digitization program and for the purpose of transition of acceptance of executive documentation (acts of performed works) from paper to digital format the platform on automation of business processes on acceptance of executive documentation on the basis of Bitrix24, with signing and coordination through EDS is developed. To date, the developed platform for automation of business processes of acceptance of executive documentation has been tested on the pilot project "Reconstruction of Karabutak-Komsomolskaya-Denisovka Rudny-Kostanay" section km 427-458 ", based on the results of which positive results were obtained and recommended for implementation. . At the same time, the eQurylys system is currently moving smoothly, which will increase the transparency of construction, strengthen control, monitor the progress of construction, create a data archive and provide access to all documents.